Real Ear Attenuation Measurements of Ear Protectors Using Ear Phones: I at Threshold - PJ, Kumar; CS, Venkatesh; Ragini (Journal of All India Institute of Speech and Hearing)
It is well known that the real ear attenuation of the hearing/ear protectors (ear plug/insert type) are measured using free-field audiometric measures. The difference in the free-field thresholds for narrow band noises at different central frequencies, measured with and without the hearing protector in the external auditory meatus of both the ears together, is considered as the real ear attenua- tion provided by those ear protectors. This attenuation, thus measured, deter- mines the attenuation characteristic of the ear protectors used.